Fazlur Rahman's Thoughts About Modernization of Islamic Education : Pemikiran Fazlur Rahman Tentang Modernisasi Pendidikan Islam - Maudy Windah Permatasari; Budi Haryanto (Academia Open, 2021)
This article aims to describe the modernization of Islamic education through the thoughts of Fazlur Rahman, so as to know Fazlur Rahman's thoughts on the modernization of Islamic education and its relevance to the modernization of Islamic education in Indonesia. The research approach used is library research whose data is obtained from a study of the literature with a character's thinking approach. The results of his research that the modernization of Islamic education according to Fazlur Rahman is an effort made by Muslim leaders to change the way of thinking, movement, and so on to give birth to scientists who are integrative, creative, innovative, honest and fair in developing Islamic education in accordance with the times. happen. While its relevance to the modernization of Islamic education in Indonesia is the establishment of many schools and universities that implement scientific integration so as to give birth to students who have the maturity of thinking in dealing with problems in this modern era.